Enhancement of kaolinite using superabsorbent polymer (SAP) as earth grounding material - Teh, Chee Yee (2017)
Earth grounding system serves as lightning-protection in industrial and power plants. One of the major parameters to determine the performance of the grounding system is the resistivity of local soil. Kaolinite has lower plasticity and lower retention of water as compared to bentonite. Thus, Superabsorbent Polymer (SAP), a material with high absorption and retention capacity of fluids is added to kaolinite to improve the performance of kaolinite in plasticity and resistivity. The main objectives of the study were to determine the improvement in the plasticity characteristic of kaolinite and establish soil-water characteristics curve (SWCC) by addition of SAP at varying percentage. This study also compare the resistivity of kaolinite at varying percentage of SAP. Three kaolinite samples are used in this study which are S300, Speswhite and FMC with the mixture 10% of SAP to determine the plasticity characteristic. The plastic limit for S300, Speswhite and FMC with addition of 10% SAP are 150.38%, 141.45% and 275.30%. The plasticity index for S300, Speswhite and FMC with 10% of SAP are 13.10%, 19.40% and 30.60% respectively. The resistivity of S300, Speswhite and FMC with 10% SAP are 130 Ω.m, 17 Ω.m and 21 Ω.m respectively. These resistivity are higher than resistivity of bentonite and Marconite, which are 6.2 Ω.m and 0.38 Ω.m.